2016
DOI: 10.1039/c6ra08699c
|View full text |Cite
|
Sign up to set email alerts
|

High performance hybrid graphene–CsPbBr3−xIx perovskite nanocrystal photodetector

Abstract: We demonstrate a highly sensitive hybrid photodetector based on graphene–CsPbBr3−xIx perovskite nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
130
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 27 publications
2
130
2
Order By: Relevance
“…However current transport experiments 21,22,23 from PNC-based devices have been performed on diode structures. 24,25 In such device geometries, the transport of the PNC layer is blurred with effects coming from the electron and hole extraction layers.…”
mentioning
confidence: 99%
“…However current transport experiments 21,22,23 from PNC-based devices have been performed on diode structures. 24,25 In such device geometries, the transport of the PNC layer is blurred with effects coming from the electron and hole extraction layers.…”
mentioning
confidence: 99%
“…CsPbBr 3− x I x and CsPbBr 3− x Cl x NCs can be obtained by halide exchange reactions between CsPbBr 3 NCs and lithium salts (LiCl or LiI). In the same group, Kwak et al prepared the graphene–CsPbBr 3− x I x perovskite NC‐based photodetector with high sensitive and demonstrated that the photoconductivity enhancement can be gained by introducing graphene with high carrier mobility. This hybrid photodetector exhibited an ultrahigh responsivity (8.2 × 10 8 A W −1 ) and an impressive detectivity (≈10 16 Jones) under 405 nm illumination (power, 0.07 mW cm −2 ).…”
Section: Hybrid Structure Of Halide‐perovskite‐based Photodetectorsmentioning
confidence: 99%
“…And a photoresponsivity over 10 5 A W −1 was achieved in graphene/CsPbBr 3 /graphene‐based phototransistor with a vertical configuration. Lee and coworkers reported an all‐inorganic CsPbBr 3− x I x perovskites/graphene photodetector with a high responsivity of 8.2 × 10 8 A W −1 and an ultrahigh detectivity of 2.4 × 10 16 Jones under 405 nm illumination (power, 0.07 mW cm −2 ).…”
Section: Hybrid Structure Of Halide‐perovskite‐based Photodetectorsmentioning
confidence: 99%
“…However,t he hybrid perovskites are quite sensitive to light, heat, and humidity,w hich greatly limited its further application for optoelectronics. [10] On the other hand, the succeeding all-inorganic perovskite CsPbX 3 (X = Cl, Br, I), which inherited the superiorities of organic-inorganic hybrid perovskites,are much more stable and thereby are outstanding candidates for optoelectronic devices.Since the first lightemitting diodes (LED) based on CsPbBr 3 quantum dots (QDs) was fabricated, [11] notable optoelectronic devices are springing up,such as solar cells, [12] CsPbX 3 nanocrystal PDs, [13] CsPb(Br/I) 3 nanorod PDs, [14] monolayer and few-layer nanosheets PDs, [15] self-healing PDs, [16] and plasmon enhanced PDs. [17] However, the performance of the PDs are generally low compared to single-crystal bulk materials.…”
mentioning
confidence: 99%
“…Although the Mie porous structure significantly increased the LH ability of the films,t he electrical transport properties are not deteriorated and the porous PDs showed high photoconductive gain of 7.63 10 5 ,h igh on/off ratio of more than 10 4 and the peak EQE value of 658 %with abias of 9Vat 520 nm, which is quite extraordinary as compared to the previous report of the all-inorganic perovskite PDs. [13,16] This new pathway of fabricating porous and interface-fused structure films with high performance have potential applications not only in planar perovskite PDs,b ut also in other optoelectronic devices,s uch as light-emitting diodes (LED), solar cells,and thin film transistors.…”
mentioning
confidence: 99%